Views of Islamic Organizations on the Tradition of Not Slaughtering Cows in Kudus - Andrea Amalia Salma; Zahrotuz Zakiyah; Zeti Pazita (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
The purpose of this study was to examine how the views of the two largest Islamic organizations in Kudus, NU, and Muhammadiyah, on the tradition of not slaughtering cows in Kudus. The background of this research is marked by the tradition of not slaughtering cows in Kudus which has existed since the time of Sunan Kudus. This type of research is qualitative research with a descriptive qualitative approach. Primary data were obtained through interviews with PCNU and PDM Kudus administrators. The results showed that the two organizations saw this tradition as a form of tolerance taught by Sunan Kudus long ago. However, regarding the preservation of this tradition, these two organizations have differences of opinion. Regarding this tradition, the NU's representative said that they prioritize morals, in this case, tolerance, compared to fiqh which is mostly khilafiyah also in this tradition, there is a value of tolerance that should be known and upheld, especially by the Kudus community. Meanwhile, Muhammadiyah itself said that this tradition concerns Tadayyun and they think that the current situation of the Da'wah map is different.